Public Pensions in a Multi-Period Mirrleesian Income Tax Model - Spencer Bastani; Sören Blomquist; Luca Micheletto (Center for Economic Studies and ifo Institute (CESifo), 2016)
Using an OLG model with skill uncertainty and private savings, we investigate whether an optimally designed set of public pension transfers can usefully supplement a nonlinear labor income tax as a welfare-enhancing policy instrument. We consider a Mirrleesian setting where agents' skills are private information and highlight that, even though pensions, by crowding out private savings, adversely affect the achievement of the golden-rule, they can be used as a mimicking-deterring device that makes it easier for the government to achieve the desired redistributive goals.
Keywords: H21; H55; H63; 330; public pensions; dynamic optimal income taxation; capital income taxation; tagging